# |
ODE |
Mathematica |
Maple |
\[
{}x -\sqrt {x^{2}+y^{2}}+\left (y-\sqrt {x^{2}+y^{2}}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \sqrt {1+y^{2}}+\left (x \sqrt {1+y^{2}}-y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}-\left (x y+x^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y-2 x^{3} \tan \left (\frac {y}{x}\right )-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{2}+y+\left (x^{3} y-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+\left (x y+\tan \left (x y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{4}-y+\left (4 x^{3} y^{3}-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{3}+y+\left (x^{3}+y^{2}-x \right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}y \left (1+y^{2}\right )+x \left (y^{2}-x +1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+\left ({\mathrm e}^{x}-y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{2}-2 y+\left (x^{3} y-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{3} y+y^{3}-\left (x^{4}+2 x y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+y \cos \left (x \right )-\sin \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (\sin \left (y\right )^{2}+x \cot \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1-\left (y-2 x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1-\left (1+2 x \tan \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (y^{3}+\frac {x}{y}\right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}1+\left (x -y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+\left (x y+y^{2}-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y = \left ({\mathrm e}^{y}+2 x y-2 x \right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (2 x +3\right ) y^{\prime } = y+\sqrt {2 x +3}
\] |
✓ |
✓ |
|
\[
{}y+\left (y^{2} {\mathrm e}^{y}-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+3 y \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (1+\cos \left (x \right )\right ) y^{\prime } = \sin \left (x \right ) \left (\sin \left (x \right )+\sin \left (x \right ) \cos \left (x \right )-y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (\sin \left (x \right )^{2}-y\right ) \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime }-y = x \left (1+x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}1+y+\left (x -y \left (1+y\right )^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y^{2} = x^{2}+1
\] |
✓ |
✓ |
|
\[
{}3 x y^{\prime }-3 x y^{4} \ln \left (x \right )-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {4 x^{3} y^{2}}{x^{4} y+2}
\] |
✓ |
✓ |
|
\[
{}y \left (6 y^{2}-x -1\right )+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) \left (y^{\prime }+y^{2}\right )-y = 0
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime }+y^{2}-\sin \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{3}-y^{4}+x y^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \tan \left (x \right )+y^{2} \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}6 y^{2}-x \left (2 x^{3}+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{3}-y {y^{\prime }}^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+{y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}x \left ({y^{\prime }}^{2}-1\right ) = 2 y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } \left (y^{\prime }+2\right ) = y
\] |
✓ |
✓ |
|
\[
{}x = y^{\prime } \sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}2 {y^{\prime }}^{2} \left (-x y^{\prime }+y\right ) = 1
\] |
✓ |
✓ |
|
\[
{}y = 2 x y^{\prime }+y^{2} {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+y^{2} = x y y^{\prime }
\] |
✗ |
✓ |
|
\[
{}2 x y^{\prime }-y = y^{\prime } \ln \left (y y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }-x^{2} {y^{\prime }}^{3}
\] |
✗ |
✓ |
|
\[
{}y \left (y-2 x y^{\prime }\right )^{3} = {y^{\prime }}^{2}
\] |
✗ |
✓ |
|
\[
{}x y^{\prime }+y = 4 \sqrt {y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }-y = \ln \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}x y^{2} \left (x y^{\prime }+y\right ) = 1
\] |
✓ |
✓ |
|
\[
{}5 y+{y^{\prime }}^{2} = x \left (x +y^{\prime }\right )
\] |
✗ |
✓ |
|
\[
{}y^{\prime } = \frac {y+2}{1+x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y-x \,{\mathrm e}^{\frac {y}{x}}
\] |
✓ |
✓ |
|
\[
{}1+y^{2} \sin \left (2 x \right )-2 y \cos \left (x \right )^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 \sqrt {x y}-y-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{\frac {x y^{\prime }}{y}}
\] |
✓ |
✓ |
|
\[
{}2 y^{2} x^{3}-y+\left (2 x^{2} y^{3}-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y-1-x y+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x \tan \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = {\mathrm e}^{x y}
\] |
✓ |
✓ |
|
\[
{}2 y-x \left (\ln \left (x^{2} y\right )-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x y+x^{3} y^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 \left (y+2\right )^{2}}{\left (x +y-1\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x}+3 y^{2}+2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y+2 x^{3} y+x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}y+3 y^{2} x^{4}+\left (x +2 x^{2} y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+\sqrt {x^{2}-y^{2}}
\] |
✓ |
✓ |
|
\[
{}2 y \left (x \,{\mathrm e}^{x^{2}}+y \sin \left (x \right ) \cos \left (x \right )\right )+\left (2 \,{\mathrm e}^{x^{2}}+3 y \sin \left (x \right )^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right )+\sin \left (y\right ) \left (x -\sin \left (y\right ) \cos \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{3}+\left (3 x^{2}-2 x y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (y^{\prime }+1\right ) \ln \left (\frac {x +y}{x +3}\right ) = \frac {x +y}{x +3}
\] |
✓ |
✓ |
|
\[
{}2 x^{3} y y^{\prime }+3 x^{2} y^{2}+7 = 0
\] |
✓ |
✓ |
|
\[
{}x -y \cos \left (\frac {y}{x}\right )+x \cos \left (\frac {y}{x}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (x y^{\prime }-y\right ) = y \left (x +y\right )
\] |
✓ |
✓ |
|
\[
{}y^{4}+x y+\left (x y^{3}-x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+3 \ln \left (y\right )-\frac {x y^{\prime }}{y} = 0
\] |
✓ |
✓ |
|
\[
{}y+\left (x y-x -y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+2 y^{3} y^{\prime } = \left (x +4 y \ln \left (y\right )\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y \ln \left (x \right ) \ln \left (y\right )+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{{3}/{2}}+x^{2}+y^{2}+2 y \sqrt {x}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +y \cos \left (x y\right )+x \cos \left (x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime }+x = 4 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}2 {y^{\prime }}^{3}-3 {y^{\prime }}^{2}+x = y
\] |
✗ |
✓ |
|
\[
{}y^{\prime }-6 x \,{\mathrm e}^{x -y}-1 = 0
\] |
✓ |
✓ |
|
\[
{}y \sin \left (x \right )+\cos \left (x \right )^{2}-\cos \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (6 y^{2}-x -1\right )+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \left (x -\ln \left (y^{\prime }\right )\right ) = 1
\] |
✓ |
✓ |
|
\[
{}\left (1+\cos \left (x \right )\right ) y^{\prime }+\sin \left (x \right ) \left (\sin \left (x \right )+\sin \left (x \right ) \cos \left (x \right )-y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x +\sin \left (\frac {y}{x}\right )^{2} \left (-x y^{\prime }+y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{4} {\mathrm e}^{y}+2 x y^{3}+y+\left (x^{2} y^{4} {\mathrm e}^{y}-x^{2} y^{2}-3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{3}-1+y^{2} y^{\prime } x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = f \left (x \right ) a
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +\sin \left (x \right )+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+3 \cosh \left (x \right )+2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a +b x +c y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a \cos \left (b x +c \right )+k y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a \sin \left (b x +c \right )+k y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a +b \,{\mathrm e}^{k x}+c y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \left (x^{2}-y\right )
\] |
✓ |
✓ |
|